2017
DOI: 10.1002/jso.24665
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic role of SF1, IGF2, Ki67, p53, adiponectin, and leptin receptors in human adrenal cortical tumors

Abstract: The presented data indicate that immunohistochemical assessment (of IGF2, SF1, Adipo R1, and R2 receptors' expression) may be useful in making the diagnosis of uncertain ACC cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
10
1
1
Order By: Relevance
“…The discovery of an adrenal tumor in imaging studies requires an assessment of its hormonal activity and of the risk of primary neoplasm as well as metastatic lesions of the adrenal gland [4,5,34,37,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The discovery of an adrenal tumor in imaging studies requires an assessment of its hormonal activity and of the risk of primary neoplasm as well as metastatic lesions of the adrenal gland [4,5,34,37,39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that adrenal tumors in patients without clinical features of hormonal disorders may exhibit subclinical adrenal hormone secretion [10,19,39,40]. Many researchers showed that incidentally dis- covered adrenal tumors are associated with increased risk of cardiovascular diseases even in cases without any clinical signs of hormonal oversecretion [22,24,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it was shown in vitro that IGF2 induces proliferation, but its overexpression does not modify the phenotypic and molecular features of ACC cells 140 . In contrast, a study that assessed IGF2 protein expression and overall survival (OS) found that high IGF2 expression is associated with longer OS, suggesting that IGF2 is not a prognostic factor for ACC progression or metastasis 141 . Only in adult ACTs were differences in IGF2 expression observed between ACA and ACC, while in pediatric ACTs, the IGF1R gene was overexpressed in carcinomas 142 .…”
Section: Adult Adrenocortical Carcinomasmentioning
confidence: 96%
“…73 only one study reported that high immunostaining of igF2 correlated with longer oS in a small group of patients (N.=20). 76 Moreover, since its high prevalence in acc, igF2 overexpression could not be useful for the classification of ACC derived by transcriptome analyses. 12 different studies demonstrated no differences in igF1 mrNa level between acc and aca or normal adrenal gland.…”
Section: The Igf System In Adult Adrenocortical Carcinomamentioning
confidence: 99%